2018
DOI: 10.22159/ajpcr.2018.v11i7.22814
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Knee Buckling Among Grade 3 Osteoarthritis Patients of Knee: A Self-Reported Study

Abstract: Objective: The present study aims to find out the sensation and frequency of episodes of knee buckling in Grade 3 osteoarthritis (OA) and its physiotherapy treatment.Methods: Experimental study design is used to determine the knee buckling in Grade 3 OA of the knee joint. Subjects are classified into two groups. Subjects with Grade 3 OA knee are examined for knee buckling. The investigator used a questionnaire to collect data from filed documents. Data were numerically coded and captured in excel, using SPSS 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…Therefore, the self-reported KI is associated with increased pain intensity, more falls, and changes in the gait pattern [27]. In another study, Lamba et al (2018) also reported that if therapeutic interventions are not performed in a timely manner, the progression of KOA over time and disease duration cause the symptoms of KI to intensify [43]. Our findings also showed that the increased duration of the disease and disease deterioration increased the risk of falling and KI.…”
Section: Discussionsupporting
confidence: 62%
“…Therefore, the self-reported KI is associated with increased pain intensity, more falls, and changes in the gait pattern [27]. In another study, Lamba et al (2018) also reported that if therapeutic interventions are not performed in a timely manner, the progression of KOA over time and disease duration cause the symptoms of KI to intensify [43]. Our findings also showed that the increased duration of the disease and disease deterioration increased the risk of falling and KI.…”
Section: Discussionsupporting
confidence: 62%